Conservation and management implications of genetic and geometric scale variation in the ancient fish giant featherback ( Chitala lopis ) - Boby Muslimin; Gunawan Muhammad; Arif Wibowo; Kurniawan Kurniawan; Vitas Atmadi Prakoso; Rendy Ginanjar; Mochammad Zamroni; Bayu Kreshna Adhitya Sumarto; Septiana Sri Astuti; Deni Irawan; Agus Priyadi; Mirna Dwirastina; et al. (Journal of Fish Biology, 2026)
Giant featherback ( Chitala lopis ) is an ancient species of freshwater fish considered globally extinct until extant populations were re‐discovered in the Sundaland region of Indonesia in 2022. To improve management of the remaining populations, this study used genomic DNA and landmark‐based geometric morphometric analyses of fish scales to evaluate whether these approaches can discriminate among phylogenetic clades, sexes and broad habitat ecotypes inhabited by extant C. lopis populations. DNA analyses of 39 specimens from eight rivers provided the first evidence of two phylogenetic clades: (i) those from Central and South Borneo and (ii) those from West Borneo, Riau, South Sumatra and Jambi. Scale morphology was characterised across eight body areas using scale dimensions (relative height and width to standard length and height‐to‐width ratio), centroid size and Procrustes shape coordinates, with repeated‐measures structure accounted for using linear mixed models and Procrustes ANOVA with a randomised residual permutation procedure (RRPP). Scale dimensions and centroid size varied significantly among body areas (all p p = 0.024), with Clade 2 individuals consistently showing lower values than Clade 1, though scale geometry overall showed limited promise as a rapid non‐destructive stock discriminator. Both clade and sex had small but significant effects on Procrustes scale shape ( R 2 = 0.015 and 0.013, respectively; both p = 0.001), while phenotypic trajectory analysis revealed that males exhibited a significantly greater amplitude of scale shape change across body positions than females (trajectory magnitude: M = 0.289, F = 0.207; p = 0.034), despite both sexes following parallel shape trajectories along the body axis. These results provide a novel morphometric baseline for C. lopis and highlight the importance of body‐position‐specific and multivariate approaches when characterising scale morphology in endangered freshwater fishes.

Comparison of black soldier fly Hermetia illucens (Diptera: Stratiomyidae) frass to chemical and organic fertilizers on arthropod abundance and edamame plant performance - Dwi Harya Yudistira; Yongki Umam Sandi; Bayu Anggita Wirabumi; Pinasindi Wikandari; Muhammad Putra Ramadhan; Dewanti Uma Rahmaningtyas; Tetsuya Fukushi; Fariz Ardiansyah Gunawan; Satoru Sato (Applied Entomology and Zoology, 2026)
The use of Hermetia illucens L. (Diptera: Stratiomyidae) larvae for the bioconversion of organic waste into protein and frass is gaining popularity. Although frass of H . illucens has been proposed as an organic fertilizer, its relative impact on crop productivity and soil organism diversity remains insufficiently understood compared to other fertilizers. We, therefore, evaluated the effectiveness of frass of H . illucens relative to commercial chemical (NPK) fertilizer and compost in edamame ( Glycine max (L.) Merr.) production while also considering their potential within the circular economy framework. Edamame plants in NPK plots averaged 71.1 ± 0.79 cm in height, which was not significantly different from frass of H . illucens plots at 69.47 ± 3.22 cm ( p > 0.05). The frass of H . illucens plots also had the highest average yield (84.27 ± 8.79 g/plant), which did not differ significantly from NPK plots (85.05 ± 7.37 g/plant) ( p > 0.05). In addition, the application of frass of H . illucens increased the abundance of soil arthropods (5.62 ± 0.99 individuals/plot), exceeding all other treatments ( p H . illucens plots (3.87 ± 0.91 individuals/plot) compared to other treatments ( p H . illucens demonstrating the highest increase across trophic levels ( p H . illucens not only enhances edamame plant growth and yield but also fosters greater soil and foliar arthropod abundance. By recycling organic waste into a valuable agricultural input, frass of H . illucens contributes to improved biodiversity and aligns with circular economy principles, offering a more sustainable approach to crop production.

Hydraulic behavior of HAWT on a small scale with differences in the blade configuration by computational method - Dewi Puspita Sari; Imam Syofii; Kaprawi Sahim; Megawati Megawati; Muhammad Alhudari; Ahmad Fudholi; Amir Arifin; Gunawan Gunawan; Dendy Adanta; Kamaruzzaman Sopian (International Journal of Energy and Water Resources, 2026)

Enhancing village-level spatial planning with unmanned aerial vehicles: A comparative study of direct georeferencing and ground control points - Gunawan Setyo Prabowo; Suprapedi Suprapedi; Muhammad Bisri; Wayan Firdaus Mahmudy; Ari Sugeng Budiyanta; Nur Sugi; Try Kusuma Wardana; Aries Asrianto Ramadian; Hartono Hartono; Rudi Choirul Anwar; Unggul Satrio Yudhotomo (Applied Geomatics, 2026)

Posterior saibo selection in the Japanese pearl oyster, Pinctada fucata martensii, as a non-genetic approach to producing high-quality cultured pearls - Suzuka Yamaoka; Gunawan Muhammad; Muhammad Helmi Fauzan; Asep Sahidin; Akira Komaru (Aquaculture International, 2025)

Tsunami hazard assessment for the Cilegon industrial zone, Java, Indonesia, by considering various digital elevation model (DEM) datasets and fault source models - Sesar Prabu Dwi Sriyanto; Arif Nurokhim; Teguh Sulistian; Indra Gunawan; Rizki Iman Sari; Brilian Tatag Samapta; Iman Fatchurochman; Fajar Triady Mugiarto; Rifqi Muhammad Harrys (Arabian Journal of Geosciences, 2024)

Batch Electrocoagulation Process for the Removal of High Colloidal Clay from Open-Cast Coal Mine Water Using Al and Fe Electrodes - Muhammad Sonny Abfertiawan; Mindriany Syafila; Marisa Handajani; Faiz Hasan; Hanifah Oktaviani; Firman Gunawan; dan Febriwiadi Djali (Mine Water and the Environment, 2024)
Open-cast coal mining operations can produce water with high amounts of total suspended solids (TSS). We tested the use of electrocoagulation for the removal of colloidal clay from mine water. Monopolar batch electrocoagulation was performed at the laboratory scale using Al and Fe electrodes and varying the DC current (0.5, 1, and 2 A) and contact time (15, 30, and 45 min). Aluminum electrode electrocoagulation with a current of 2 A and a contact time of 15 min had the greatest TSS removal efficiency (99%), with concentrations decreasing from 5,400 to 23 mg/L. The greatest removal (98 and 99%, respectively) was obtained using an Al electrode with an electric current of 0.5 and 1 A, with 30 min of contact time. With an Fe electrode, the greatest efficiency was achieved with a current of 2 A and a contact time of 30 min. The TSS removal efficiency reached 98% while the concentration dropped to 66 mg/L, followed by 89% and 95% for the 0.5 A-45 min and 1 A-15 min variations, respectively.

Influence of geographical origin and shell positions on nacre color and thickness in mabé pearl oysters Pteria penguin - Tracy Aisea; Gunawan Muhammad; Asep Sahidin; Akira Komaru (Aquaculture, 2024)

How the mantle location from which saibo is cut affects cultured Pinctada fucata martensii pearl quality - Gunawan Muhammad; Asep Sahidin; Dien Arista Anggorowati; Akira Komaru (Aquaculture International, 2024)

Dynamics of the Young Merapi (<2.2 ka – 1,788 CE) pumice fall deposits: Insights from textural and geochemical studies - Indranova Suhendro; Gabriela Nogo Retnaningtyas Bunga Naen; Andriansyah Gurusinga; Sistien Adhaena Sari; Mradipta Lintang Alifcanta Moktikanana; Rachmi Mustika Pertiwi Putri Gunawan; Jesslyn Jane; Muhammad Fatih Qodri; Faraz Sya'bana; Sherinna Mega Cahyani; Dini Nuari Ardian (Journal of Volcanology and Geothermal Research, 2023)

Anti-Inflammatory, Antioxidant, Metabolic and Gut Microbiota Modulation Activities of Probiotic in Cardiac Remodeling Condition: Evidence from Systematic Study and Meta-Analysis of Randomized Controlled Trials - Nurpudji Astuti Taslim; Muhammad Yusuf; Ade Meidian Ambari; Imke Maria Del Rosario Puling; Filzatuz Zahro Ibrahim; Hardinsyah Hardinsyah; Rudy Kurniawan; William Ben Gunawan; Nelly Mayulu; Victor F. F. Joseph; Nindy Sabrina; Mochammad Rizal; et al. (Probiotics and Antimicrobial Proteins, 2023)
Heart failure (HF) is a global pandemic with increasing prevalence and mortality rates annually. Its main cause is myocardial infarction (MI), followed by rapid cardiac remodeling. Several clinical studies have shown that probiotics can improve the quality of life and reduce cardiovascular risk factors. This systematic review and meta-analysis aimed to investigate the effectiveness of probiotics in preventing HF caused by a MI according to a prospectively registered protocol (PROSPERO: CRD42023388870). Four independent evaluators independently extracted the data using predefined extraction forms and evaluated the eligibility and accuracy of the studies. A total of six studies consisting of 366 participants were included in the systematic review. Probiotics are not significant in intervening left ventricular ejection fraction (LVEF) and high-sensitivity C-reactive protein (hs-CRP) when compared between the intervention group and the control group due to inadequate studies supporting its efficacy. Among sarcopenia indexes, hand grip strength (HGS) showed robust correlations with the Wnt biomarkers ( p < 0.05), improved short physical performance battery (SPPB) scores were also strongly correlated with Dickkopf-related protein (Dkk)-3, followed by Dkk-1, and sterol regulatory element-binding protein 1 (SREBP-1) ( p < 0.05). The probiotic group showed improvement in total cholesterol ( p = 0.01) and uric acid ( p = 0.014) compared to the baseline. Finally, probiotic supplements may be an anti-inflammatory, antioxidant, metabolic, and intestinal microbiota modulator in cardiac remodeling conditions. Probiotics have great potential to attenuate cardiac remodeling in HF or post-MI patients while also enhancing the Wnt signaling pathway which can improve sarcopenia under such conditions.

Seasonal groundwater salinity dynamics in the mangrove supratidal zones based on shallow groundwater salinity and electrical resistivity imaging data - Joko Prihantono; Takashi Nakamura; Kazuo Nadaoka; Tubagus Solihuddin; Dino Gunawan Pryambodo; Muhammad Ramdhan; Novi Susetyo Adi; Ilham; Anindya Wirasatriya; Sugeng Widada (Wetlands Ecology and Management, 2023)
Soil salinity plays an essential role in the growth of mangroves. Mangroves usually grow in intertidal zones. However, in Karimunjawa National Park (KNP), Indonesia, mangroves are also found in supratidal zones. Thus, this study aims to determine why mangroves can grow in this supratidal zone, even during the dry season. We analyze seasonal changes in groundwater flow and salinity dynamics using the hydraulic head, shallow groundwater salinity, and electrical resistivity imaging (ERI) data. The result shows that variation in groundwater salinity is caused by seawater intrusion, which is generated by a hydraulic gradient due to the sea level being higher than the water table in KNP. Rainfall and evapotranspiration, which change seasonally, likely affect the water table fluctuation and salt concentration. ERI images indicate this seawater intrusion in the top sediment up to the bedrock boundary. However, the resistivity difference in the wet and dry seasons shows that remarkable resistivity change occurs at the deeper layer (50–60 m below ground level (BGL)), likely due to freshwater recharge from rainwater on the land side. Groundwater in the KNP is shallow and saline; thus, mangroves in this zone, e.g., Ceriops tagal and Lumnitzera racemosa , can grow because their roots can reach this groundwater. These mangrove species can still grow in this zone even though the shallow groundwater is very saline (46–50 ppt). However, this condition might cause these mangroves to grow stunted. Thus, freshwater availability is crucial for mangrove growth in this supratidal zone to dilute this high groundwater salinity.

Two new 2-arylbenzofurans from Sesbania grandiflora L. and their cytotoxicity towards cancer cell - Tjitjik Srie Tjahjandarie; Mulyadi Tanjung; Ratih Dewi Saputri; Devina Oktari Rahayu; Alfiah Nur Irza Gunawan; Muhammad Fajar Aldin (Natural Product Research, 2021)